Development and testing of a bioreactor for production of hydrogen - Kalala, Bukasa (My University, 2009)
A laboratory-scale anaerobic Fluidised Bed Bioreactor (FBBR) was designed and constructed for hydrogen gas (H2) production using a sucrose-based synthetic wastewater. In the first experiment, the anaerobic FBBR was inoculated with two facultative anaerobic bacteria Citrobacter freundii (Cf1) (Accession number: EU046372) and Enterobacter cloacae (Ecl) (Accession number: EU046373) to study their H2 productivity capacity. Granulated activated carbon was used to initiate the growth and development of bacterial granules. For granule production the hydraulic retention time (HRT) was gradually reduced from 8 to 0.5 h. Hydrogen production and sucrose consumption was investigated at HRTs ranging from 8 to 0.5 h. Sucrose was converted into volatile fatty acids (VFAs) and biogas (essentially H2). Temperature and pH of the anaerobic FBBR were controlled at 37±1ºC and 5.6±0.1 respectively. The H2 production rate (HPR) reached 138mmol/(h.L) at 0.5 h HRT. Acetic, butyric and propionic acids were detected at 104.5±21.06, 76.13±16.81 and 24.91±2.67 mg/L respectively. Results showed that Ecl and Cf1 were able to convert sucrose into soluble and biogas products with high rate of H2 gas production. In the second experiment, a heat and acid treated sample of activated sewage sludge from an anaerobic sewage works was used as the inoculum for growing the granular bed in the anaerobic FBBR. The anaerobic FBBR was operated according to conditions described in the first experiment. HPR reached a maximum of 130.1 mmol/(h.L) at 0.5 h HRT with constant influent sucrose concentration of 17.65 g/L. In both experiments the influent sucrose concentration in the bioreactor expressed in terms of chemical oxygen demand (COD) was 20 gCOD/L. Optimal sucrose to hydrogen ration was observed at a HRT of 2 h and led to a H2 yield (YH2) of 1.61 mmol-H2/mmol-sucrose.